Penentuan Skala Prioritas Pengembangan Potensi Mata Air untuk Irigasi Menggunakan Metode TOPSIS di Kecamatan Singosari Kabupaten Malang - Ni Luh Putri Prabandari; Hari Siswoyo; Riyanto Haribowo (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The objective of this study was to determine the order of priority for the development of potential springs as a source of irrigation water using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. This research was conducted in 11 locations of springs in Singosari District, Malang Regency. The spring potential assessment was carried out using 4 criteria consisting of water quantity, water quality, flow continuity, and irrigation area. The quantity of water at the research site is in the range of 8 liters/second – 45,180 liters/second. The water quality of the 11 springs is in the same class, namely C2-S1 with medium salinity hazards and low alkalinity hazards. There were 7 springs with annual flow and 4 springs with seasonal flow. The irrigated area in the study area ranged from 0.12 ha to 98 ha. The order of priority for the 3 highest springs to be developed based on the minimum discharge, namely Umbulan Spring, Sekaran Spring, and Pakisuceng Spring, while based on the maximum discharge, namely Umbulan Spring, Suko Spring, and Petung Wulung Spring.